Skin adnexal tumors: a 5 years single institutional experience - Shanmugam, Subbiah; Alluru, Jagadish Singh; Mendu, Samanth Kumar (International Journal of Research in Dermatology, 2020)
Background: Skin tumors comprise of innumerable benign and malignant lesions. They vary in behaviour and malignant potential. Apart from more common melanomatous and squamous cell carcinomas, there exist unexplored arena of adnexal tumors that are rare and most often pose a dilemma for treating doctor. Their demography and presentation are yet to be standardized globally. Methods: This is a cross-sectional descriptive study undertaken in department of surgical oncology, government Royapettah hospital, Chennai from January 2013 to 2019, primarily focused to analyze the various cutaneous adnexal tumors with regard to age, sex, site, size, behavior, origin of these tumors and to correlate with the clinical presentation. Descriptive characteristics like frequencies were computed for categorical variables like gender, histologic diagnosis, primary site of disease, and type of surgical treatment, while numeric variables were summarized using mean with standard deviation, median and range. Results: Thirteen cutaneous adnexal lesions were reported in the past 5 years at our institute. Out of the 13 cases two were benign and eleven were of malignant skin adnexal tumors. Sweat gland tumors were the most common tumors encountered and were found to be more common in males below age of 60, trunk being common site of occurrence. Conclusions: One should have high index of suspicion, aided by proper histopathology followed by aggressive treatment is necessary for proper control. Most of them need adjuvant treatment. No standardized treatment poses some problem, that needs to be addressed with proper documentation.